PENGARUH PENGEMBANGAN KARIR KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DITJEN PAJAK YANG DIMODERASI LINGKUNGAN KERJA (Studi Pada Kantor Pelayanan Pajak Madya Semarang) - Rokhim, 12 4202 0048; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to determine the effect of career development, competence and compensation on employee performance are moderated Taxation Office Environments Office Tax Associate at Semarang. The primary data used in this study is the result of questionnaires career development, competencies, compensation, employee performance and work environment. Sources of data in this study amounted to 106 employees from various sections in the Tax Office Associate Semarang. Analysis of the data in this study using multiple regression analysis using software IBM SPSS.19. Based on the analysis of the data found that career development does not significantly influence the performance of tax officials Semarang Associate Tax Office. Competence and compensating positive effect on employee performance. Work environment moderate the career development on employee performance and compensation, work environment  while  not   moderate  competence on employee performance. Key words: career development, competencies, compensation, work environment and employee performance